Aplikasi Manajemen Keuangan Pribadi Berbasis Mobile Menggunakan Framework Flutter - Isnaeni, Tubagus Muchamad; Angraina Fitri, Diah; Musyarrofah, Ofah; Ilhammullah, Ilhammullah (Computer Science and Information Technology, 2025)
Personal financial management is a crucial aspect of maintaining individual financial stability. However, many people struggle to effectively record, manage, and monitor their income and expenses. This research aims to develop a mobile-based financial management application using the Flutter Framework, focusing on simple record-keeping (CRUD) features. It also features transaction categories, monthly summaries, and the user's final balance. This application is designed to help users easily record income and expenses, display a list of transactions, and allow for editing and deletion of data. With a minimalist approach, this application does not require an online connection, allowing it to be used offline and ensuring user data privacy. The database system used is SQLite, which is lightweight and suitable for mobile applications. The development method used is the Waterfall method, which includes requirements analysis, system design, implementation, testing, and maintenance. Test results show that this application is able to meet basic financial record-keeping needs with a simple and responsive interface. This application is expected to provide a practical solution for individuals seeking a simple financial management tool and serve as a foundation for the development of more complex features in the future.